2011
DOI: 10.1103/physrevb.84.155420
|View full text |Cite
|
Sign up to set email alerts
|

Landau levels, edge states, and strained magnetic waveguides in graphene monolayers with enhanced spin-orbit interaction

Abstract: Citation: De Martino, A., Hütten, A. and Egger, R. (2011). Landau levels, edge states, and strained magnetic waveguides in graphene monolayers with enhanced spin-orbit interaction. Physical Review B (PRB), 84(15), doi: 10.1103/PhysRevB.84.155420 This is the unspecified version of the paper.This version of the publication may differ from the final published version. The electronic properties of a graphene monolayer in a magnetic and a strain-induced pseudomagnetic field are studied in the presence of spin-or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 66 publications
3
43
0
Order By: Relevance
“…It exhibits many unusual physical properties, e.g., a rich magnetic quantization [1][2][3][4][5][6][7][8], half-integer Hall effect [9][10][11][12][13][14][15][16], high Young's modulus [17][18][19][20][21], high Fermi velocity (10 6 m/s), and others. Graphene could play an important role in technological applications such as electric circuits [22,23], field-effect transistors [24,25], light-emitting diodes [26][27][28], solar cells [29][30][31][32], and durable touch screens [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…It exhibits many unusual physical properties, e.g., a rich magnetic quantization [1][2][3][4][5][6][7][8], half-integer Hall effect [9][10][11][12][13][14][15][16], high Young's modulus [17][18][19][20][21], high Fermi velocity (10 6 m/s), and others. Graphene could play an important role in technological applications such as electric circuits [22,23], field-effect transistors [24,25], light-emitting diodes [26][27][28], solar cells [29][30][31][32], and durable touch screens [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…The present contribution reports results obtained by the authors in [19]. The structure is as follows.…”
Section: Introductionmentioning
confidence: 94%
“…For details about the solutions and the solutions for a negative magnetic field (i.e., ε = −1), see Ref. [19]. Next, we analyze the spatially uniform case.…”
Section: General Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent investigations of the interplay between QH and QSH phases in some specific examples of 2DDFGs [20][21][22][23] have led to surprising results. In these works, it was shown that the QSH phase can survive the presence of a perpendicular magnetic field and that the Z 2 topological invariant [4] remains non-trivial for energies below the spin-orbit induced gap, despite the breaking of timereversal symmetry [59].…”
Section: Graphenementioning
confidence: 99%